The Impact of Cannabis Abuse on Psychotic Symptoms and Their Severity among Cannabis Associated Psychosis Subjects: An Indian Experience - Ramchandra Lamba; Sona Budaniya; Rajendera Kumar Acharya; Ram Kumar Solanki; Ashok Kumar (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
Use of cannabis for recreational, religious and cultures has been prevalent since ancient times. It is one of the commonest used illicit substance. While not all cannabis users develop psychiatric problems, heavy cannabis use may increase the risk of cognitive abnormalities, psychotic illness and mood disorders. This research aimed to evaluate severity of various psychotic symptoms in relation to variables of cannabis abuse. A cross sectional study of 30 male patients admitted at tertiary care psychiatric center with diagnosis of cannabis-associated psychosis was carried out. Cannabis abuse variables along with psychotic symptoms severity on BPRS scale were obtained. Correlation between variables of cannabis abuse and psychotic symptoms and total BPRS score were derived using Pearson correlation 2- tailed test. Hostility (83%) and excitement (77%) were most prevalent symptoms with increased severity followed by elevated mood, grandiosity, suspiciousness and motor hyperactivity. Patients with long duration and early onset of cannabis abuse presented with more severe form of psychosis. Frequency of cannabis use was not significantly correlated with total BPRS score, although amount spent over cannabis was significantly associated with total BPRS score. Family history of cannabis abuse predicted early onset of cannabis abuse.